Does national culture affect integrated reporting quality? A focus on GLOBE dimensions - Nicola Raimo; Marianna Zito; Alessandra Caragnano (9th International Symposium on Natural Resources Management, May 31st, 2019, Zajecar, Serbia, 2019)
Integrated reporting (IR) is a new form of corporate reporting that aims to provide a holistic picture of an organisation's performance. A critical aspect of IR is the quality of the reports. Although several studies investigate IR, few focus on quality. This study investigates the impact of national culture on IR quality. The results show that IR quality is related to six GLOBE dimensions. Specifically, the results indicate that assertiveness, institutional collectivism, uncertainty avoidance and humane orientation are positively associated to IR quality while performance orientation and future orientation are negatively associated with it. This study contributes to the relevant literature by analysing an additional factor that influences the integrated reporting quality.
Keywords: 330; integrated reporting; GLOBE; national culture; sustainability reporting; corporate reporting